Transcriptomic similarities and differences between the limb bud AER and unique carapacial ridge of turtle embryos. Issue 5 (30th August 2020) - Cordero, Gerardo A.
Abstract: Evolutionary innovation may arise via major departures from an ancestral condition. Turtle shell morphogenesis depends on a unique structure known as the carapacial ridge (CR). This lateral tissue protrusion in turtle embryos exhibits similar properties as the apical ectodermal ridge (AER)—a well‐known molecular signaling center involved in limb development. Still, how the CR influences shell morphogenesis is not entirely clear. The present study aimed to describe the CR transcriptome shortly before ribs were halted within its mesenchyme, as required for shell development. Analyses exposed that the mesenchymal marker VIM was one of the most highly co‐expressed genes and numerous appendage formation genes were situated within the core of CR and AER co‐expression networks. However, there were tissue‐specific differences in the activity of these genes. For instance, WNT5A was most frequently assigned to appendage‐related annotations of the CR network core, but not in the AER. Several homeobox transcription factors known to regulate limb bud patterning exhibited their highest expression levels in the AER, but were underexpressed in the CR. The results of this study corroborate that novel body plans often originate via alterations of pre‐existing genetic networks. Altogether, this exploratory study enhances the groundwork for future experiments on the molecular underpinnings of turtle shell development and evolution. Abstract : Highlight: Turtle shell formation is made possible by the unique carapacial ridge (CR). Here, I describe first the transcriptome of the CR and compare it to the apical ectodermal ridge, which is a well‐known molecular signaling of the embryonic limb.